Marketing Library and Information Services - Saur, K.G. (IFLA, 2012)
Framing sound marketing principles within the context of customer service, Weingand demonstrates how current marketing ideas and strategies can contribute to effective library and information center management. This new edition of Weingand's practical handbook gives a broad overview of the entire marketing/planning system-from a working definition of marketing, creating a marketing team, and developing a mission to conducting a marketing audit, setting goals, creating an action plan, designing and pricing the product, connecting to customers, promoting services, and evaluating the end result.